Constructive Side-Channel Analysis and Secure Design Third International Workshop, COSADE 2012, Darmstadt, Germany, May 3-4, 2012. Proceedings - Schindler, Werner; Huss, Sorin A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the Third International Workshop on Constructive Side-Channel Analysis and Secure Design, COSADE 2012, held in Darmstadt, Germany, May 2012. The 16 revised full papers presented together with two invited talks were carefully reviewed and selected from 49 submissions. The papers are organized in topical sections on practical side-channel analysis; secure design; side-channel attacks on RSA; fault attacks; side-channel attacks on ECC; different methods in side-channel analysis.
Keywords: Computer science; Computer communication systems; Computer security; Data encryption (Computer science).; Algorithms; Computers and civilization; Management information systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Systems and Data Security; Computers and Society; Electronic books